Psychosocial Problems on Adolescents with Thalassemia Major: A Systematic Scoping Review - Mardhiyah, Ai; Suzana Mediani, Henny; Letcmi Panduragan, Santhna; Yosep, Iyus (KnE Social Sciences, 2023)
Disease and treatment of thalassemia major that are carried out for life can cause physical and psychological problems in sufferers. Adolescents with thalassemia major will experience disturbances at a stage of development that is undergoing dynamic changes. Nurses, as health workers who provide holistic services, need to know what psychosocial problems may arise in adolescents with thalassemia major. This study aims to describe psychosocial problems in adolescents with thalassemia major. This study uses a scoping review design by searching English literature through the CINAHL, PubMed, and Scopus databases. The keywords used are psychosocial problems, thalassemia major, and adolescence. The criteria for the article in this study where the patient was a teenager with thalassemia, open access full text, and the time setting was the last 10 years (2013-2022). We found 9 articles discussing psychosocial problems in adolescents with thalassemia. Psychosocial problems that arise in the form of disturbances in several functions, namely physical, emotional, social, and school functions. Psychosocial disorders that occur in adolescents with thalassemia cause disturbances at the stage of adolescent development. Psychosocial problems that occur in adolescents with thalassemia include impaired physical, emotional, social, and school functions. Keywords: adolescence, psychosocial problems, thalassemia major